Investigation of the relationship between atherosclerosis and interleukin-6 -174G⁄C gene polymorphism - Sanrı, Umut Serhat (The European Research Journal, 2020)
Objectives: Atherosclerosis is a chronic disease that causes various cardiovascular complications. The onset and progression of atherosclerosis depends primarily on genetic factors and life style, but the underlying cellular and molecular mechanisms are still unclear. In recent studies, circulating cytokines have been shown to play an important role in inflammatory events. Interleukin-6 (IL-6) plays an important role in the regulation of proinflammation. In this study, a single nucleotide polymorphism of IL-6 gene at position -174 was studied. Our aim was to investigate the relationship between IL-6 -174G/C polymorphism and atherosclerosis. Methods: In this prospective randomized study, 104 patients were included in both groups. We used Polymerase Chain Reaction-Restriction Fragment Lenght Polymorphism (PCR-RFLP) method to amplify the polymorphism region. Results: Allele frequency distributions of IL-6 -174G/C polymorphism in the study and control groups were evaluated. There were no statistically significant diversity between A and B allele frequencies. Conclusions: The allele frequency and genotype distribution between the groups was not statistically different, which indicates another mechanisms on regulation of these cytokines. Single gene polymorphisms are generally not reproducible. Therefore, broad-based studies should be carried out considering suitable conditions and multi-factor features.